ANALISIS KONSEP DASAR PENGANTAR AKUNTANSI DALAM DUNIA BISNIS - Jaka Bagja (Jurnal Ekonomi dan Bisnis, 2026)
Accounting plays an important role in the modern business world as an information system that provides accurate, relevant, and reliable financial data to support economic decision-making. This study aims to analyze the basic concepts of introductory accounting and its role in supporting business management in the modern era. The research method used is a qualitative approach with a literature research design (library research). Data were obtained through literature studies from various sources such as books, scientific journals, and relevant academic documents, and then analyzed using content analysis techniques. The results of the study show that introductory accounting includes basic concepts that serve as the foundation for financial recording and reporting processes, namely the economic entity concept, going concern concept, accounting period concept, monetary unit concept, and double-entry system. In addition, this study explains the stages of the accounting cycle, which include identifying transactions, recording in journals, posting to the general ledger, preparing a trial balance, and preparing financial statements. Introductory accounting also plays a role as a basis for decision-making, a financial control tool, a means of accountability, a support for business technology development, and an enhancer of corporate financial transparency.